2016
DOI: 10.1021/acssynbio.6b00178
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Core Promoters as Universal Parts for Fine-Tuning Expression in Different Yeast Species

Abstract: Synthetic biology and metabolic engineering experiments frequently require the fine-tuning of gene expression to balance and optimize protein levels of regulators or metabolic enzymes. A key concept of synthetic biology is the development of modular parts that can be used in different contexts. Here, we have applied a computational multifactor design approach to generate de novo synthetic core promoters and 5′ untranslated regions (UTRs) for yeast cells. In contrast to upstream cis-regulatory modules (CRMs), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 64 publications
1
76
0
1
Order By: Relevance
“…This vector contains integration sequences near the ARG4 locus and was linearized with Swa I to target insertion near the ARG4 locus, as had been well established for promoter characterizations in P. pastoris 30,39,41 . Also the following vectors described below were based on this vector backbone.…”
Section: Methodsmentioning
confidence: 99%
“…This vector contains integration sequences near the ARG4 locus and was linearized with Swa I to target insertion near the ARG4 locus, as had been well established for promoter characterizations in P. pastoris 30,39,41 . Also the following vectors described below were based on this vector backbone.…”
Section: Methodsmentioning
confidence: 99%
“…We aimed to investigate specific/nonspecific integration, hence we transformed small amounts of DNA to avoid the pronounced occurrence of multicopy integrations. Previous studies with reporter plasmids from the pPpT4 family (28)(29)(30) showed that 1 g of linearized vector DNA resulted in an even expression landscape, i.e., similarly expressing clones. Hence, we also used amounts equivalent to 1 g of the reference constructs from references 28-30.…”
Section: Discussionmentioning
confidence: 99%
“…While these integration events can have a profound influence on strain productivity and physiology, it remains partly unclear to what extent they occur, how they are influenced by expression cassette properties, and how they bias typical standard expression approaches in P. pastoris. For comparisons of different enzyme variants (e.g., from natural variants or protein engineering efforts) or promoter variants (e.g., to fine-tune expression [28][29][30]), it is necessary to perform multiple transformations for each clone expressing a different gene. Expression from the actual transformants used for comparisons may be biased by clonal variation to an unknown extent, possibly influencing the interpretation of the study if only a limited number of transformants are tested.…”
mentioning
confidence: 99%
“…Promoter engineering includes approaches such as chimeric promoter design (Blazeck, Garg, Reed, & Alper, 2012;Blazeck, Liu, Redden, & Alper, 2011), random mutagenesis (Alper, Fischer, Nevoigt, & Stephanopoulos, 2005;Portela, Vogl, Ebner, Oliveira, & Glieder, 2018;Qin et al, 2011), modification of transcription factor binding sites (Ata et al, 2017;Hartner et al, 2008;Prielhofer et al, 2018), and synthetic promoter design (Curran et al, 2014;Portela et al, 2017;Redden & Alper, 2015;Vogl, Ruth, Pitzer, Kickenweiz, & Glieder, 2014). Synthetic biology extends on promoter engineering aiming to increase the transcription rate through designing regulatory circuit(s) by engineering binding of activating TF(s).…”
Section: Introductionmentioning
confidence: 99%